Competition for in Vitro [(3)H]Gibberellin A(4) Binding in Cucumber by Substituted Phthalimides: Comparison with in Vivo Gibberellin-Like Activity - Yalpani, Nasser (1989)
Certain N-substituted phthalimides (NSPs) have gibberellin (GA)-like activity in a number of GA bioassays. The interaction between representative NSPs and a protein fraction from cucumber (Cucumis sativus L.) hypocotyls that has GA-binding characteristics consistent with those expected of GA receptors was studied. Analysis of in vitro equilibrium saturation data indicated the presence of only one class of high affinity [(3)H]GA(4) binding sites (K(d) ∼ 30 nanomolar, n = 0.25 picomole per milligram of protein). In the presence of 6 or 60 micromolar 1-[3-chlorophthalimido]-cyclohexanecarboximide (AC-94,377), the K(d) for [(3)H]GA(4) increased, whereas the maximum number of saturable [(3)H]GA(4) binding sites did not change significantly. The dissociation of [(3)H]GA(4) from its binding sites was complex and was best described by a bi-exponential equation. AC-94,377 did not affect the rates of [(3)H]GA(4) dissociation from its binding sites. These results implied that AC-94,377 and [(3)H]GA(4) compete for binding to the same sites. A correlation was observed between the activity of over 20 NSPs in the cucumber hypocotyl bioassay and their in vitro affinity for the GA binding sites. Our observations lend further support to the notion that certain GA binding proteins in cucumber cytosol are GA receptors and also provide a molecular explanation for the GA-like in vivo activity of some NSPs.